Association between antimicrobial usage and resistance on commercial broiler and layer farms in Bangladesh - Foysal, Mohammad; Imam, Tasneem; Das, Shetu B.; Gibson, Justine S.; Mahmud, Rashed; Gupta, Suman D.; Fournié, Guillaume; Hoque, Md. Ahasanul; Henning, Joerg (Frontiers in Veterinary Science, 2024)
Antimicrobial resistance has emerged as a significant health problem worldwide, including in Bangladesh, where chickens are an important protein source for human nutrition. One of the factors accelerating the development of antimicrobial resistance is the inappropriate use of antimicrobials on commercial chicken farms.A cross-sectional study was conducted in 2019 on 140 commercial chicken farms in the Chattogram district of Bangladesh to investigate the association of antimicrobial use and resistance in Escherichia coli and Salmonella spp. cultured from cloacal swabs of chickens and the poultry shed environment.All E. coli and Salmonella spp. isolates were resistant to multiple antimicrobial classes, including those categorised as "Highest Priority Critically Important Antimicrobials" for human medicine. Notably, resistance was observed in E. coli isolates from farms that did not use these antimicrobial classes in the current production cycle. For example, although quinolones were not used on 43.9% of E. coli positive farms, 95.7% of these farms had quinolone-resistant E. coli isolates. The results of the path analysis revealed that there was a 'direct effect' of the frequency of antimicrobial usage on "high" resistance with resistance increasing when antimicrobials were administered more frequently (β=0.28, p=0.002). There was a 'direct effect' of the purpose of antimicrobial use on "low" resistance when resistance marginally decreased when antimicrobials were administered solely for therapeutic use (β=-0.17, p=0.062), but increased when they were used prophylactically.Overall, the study results could be used to educate farmers on better practices for antimicrobial administration, and to guide government agencies to update policies on antimicrobial use and resistance surveillance in the poultry sector of Bangladesh.